1991
DOI: 10.5380/abpr.v20i0.766
|View full text |Cite
|
Sign up to set email alerts
|

Condição da colônia e alterações bionômicas em Geotrigona inusitata (Apidae, Meliponinae)

Abstract: Condição da colônia e alterações bionômicas em Geotrigona inusitata (Apidae, Meliponinae)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1
4

Year Published

1998
1998
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 0 publications
0
14
1
4
Order By: Relevance
“…Usually, weaker colonies produce smaller bees than their stronger counterparts (Lacerda et al, 1991) and larger bees forage earlier (Käpylä, 1974), a fact confirmed by Hilário et al (1998), through chronobiological analysis of Melipona bicolor bicolor. However, the pollen collection pattern in both colonies changed according to the length of the day and climatic period considered.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Usually, weaker colonies produce smaller bees than their stronger counterparts (Lacerda et al, 1991) and larger bees forage earlier (Käpylä, 1974), a fact confirmed by Hilário et al (1998), through chronobiological analysis of Melipona bicolor bicolor. However, the pollen collection pattern in both colonies changed according to the length of the day and climatic period considered.…”
Section: Discussionmentioning
confidence: 53%
“…However, the external activity depends on the body size of the insects. Larger species usually fly at lower temperatures and light intensities than their smaller counterparts (Käpylä, 1974) and strong colonies produce larger bees than the intermediate and weak ones (Lacerda et al, 1991). In Melipona bicolor bicolor, foragers of stronger colonies begin flight activity earlier and at lower temperatures than those of intermediate and weak colonies (Hilário et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…They verified that the smaller bees carried more pollen in each trip than the larger ones, and that bees of weak colonies also brought more pollen in each trip in relation to the weight than bees of strong colonies. Lacerda et al (1991) also mentioned that weak colonies of Geotrigona inusitata produced smaller bees than the strong ones.…”
Section: Introductionmentioning
confidence: 99%
“…Camillo-Atique (1974 verified the influence of the strength of the colonies in the behavior of Melipona rufiventris and Friesella schrottkyi. Lacerda et al (1991) discussed for Geotrigona inusitata behavioral changes in weak, medium and strong colonies based on the variation of the population size of the nests, having mentioned alterations in the workers size and in the flight activity, although this last aspect has not been quantified. Kleinert-Giovannini & Imperatriz-Fonseca (1986) had already verified that external activity could be influenced by the strength of the colony.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, regardless of the characteristics of the resource and habitat, the individual´s body size can also be determinant in their ability to exploit resources (Mittelbach 1981, Ramalho et al 1994. Size variation of worker, within-colony, is well documented for the Apidae group, including the stingless bees Meliponinae (Lacerda et al 1991). For most organisms, the largest individuals are generally stronger and more experienced, and could therefore indicate a greater capacity for carrying and manipulating resources (Schoener 1971, Polis 1984.…”
mentioning
confidence: 99%